Are direct payments for environmental services spelling doom for sustainable forest management in the tropics? - Wunder, Sven (2006)
Over the past several decades, significant donor funding has been directed to sustainable forest management in the tropics, in the hope of combining forest conservation with economic gains through sustainable use. To date, this approach has produced only modest results in terms of changed silvicultural and land-use practices in this area. Direct payments for environmental services (PES) have been suggested as a promising alternative but still remain widely untested in the tropics. This paper first provides a conceptual assessment of PES, comparing the main features of this practice with those of other conservation instruments. Second, the paper discusses a series of critical questions that have been raised about both the environmental and livelihood impacts of PES. It is concluded that some ex ante judgments about the effects of PES may have been overly critical, and that, based on preliminary assessments, there is good reason to continue experimental PES implementation for purposes of consolidating our knowledge.